The Application of an Expressive Arts Activity for the very First Session of Training of Personal and Professional Development of Cognitive-Behavioural Clinical Psychologists: Cognitive Content as Proxy Data to Study Core Beliefs - Bertelli, Rosangela (Advances in Social Sciences Research Journal, 2019)
Cognitive-behavioural psychotherapies are evidence based interventions which are carried out thorough the examination of proxies such as automatic thoughts which could be thought of as memories of the past pointing towards one’s core beliefs. Expressive arts activities were applied in the first session of training of cognitive-behavioural personal and professional development of 67 master’s degree students in clinical psychology. The students were instructed to colouring outlines of images and at the same time quietly watch their streaming of thoughts without making judgements or replying to those thoughts. At the end of the expressive arts activity they had the opportunity to write down and report on their mental experiences. Such reports were filled with proxies and were properly examined. Results revealed contents concerning recollections about family and longing for family, responsibilities and expectations tilted towards family, and very few instances of consciousness and comprehending (“…I allowed myself to follow those running automatic thoughts…”). Considering these results, in order for the prediction that the coming of this (humankind) geological force’s self-awareness to come true it would require from humankind a deep understanding of nature, including an extremely sharp and strongly felt self-understanding, and the transcendence of thought itself.